ANNOTATION OF NON-CODING REGIONS OF STREPTOCOCCI FAMILY: A CASE STUDY - ONDARI NYAKUNDI ERICK (International Journal of Pharma and Bio Sciences, 2013)
Non-coding functional elements recently have proved to play vital functions in eukaryotes worthy ignoring in the prokaryotic counter parts. We argue that elucidating these non-coding elements will lead to a better understanding of the differences co-existing between the Streptococci species, an important human pathogen responsible for vast diseases devastating the economy. The study analyzed 56 strains from NCBI, where 44,523 sequences were extracted by PERL script. Similarity search by Blast, Genemark and CPC revealed a total of 1443 potential sequences preceding functional studies by deploying Pfam, InterproScan and COG depicting 144 proteins allowing them to be designated as novel ones. The results potentially could be used as new vaccine targets, better understanding of the different biological niches; re-annotation also can be looked unto for potential genomic island identification and further wet-lab extensions research work for better understanding of the Streptococci family for further directions and incorporation of the identified proteins into database.